Language innovations in documentary 33 (2013)
The documentary 33 was amply study for researches on the audiovisual camp, but still not receive as philosophy of analysis one mix between the audiovisual narrative and transmedia storytelling. This article present, from previous study about the theme, results of one detailed analysis about the mix of two narratives in the film 33, by Kiko Goifman. Expected, from this article, that adopts as methodologies the film analysis and qualitative study, present subsidies for better comprehension not only about the film, but also about the mix of two narratives, fundamental concern for the contemporary audiovisual communication. Copyright © 2013 (Eugene Loos).